Involvement of the Avian Dorsal Thalamic Nuclei in Homing Pigeon Navigation - Jorge, Paulo E.; Pinto, Belmiro V.; Bingman, Verner P.; Phillips, John B. (Frontiers in Behavioral Neuroscience, 2017)
The navigational ability of birds has been a focus of popular and scientific interest for centuries, but relatively little is known about the neuronal networks that support avian navigation. In the brain, regions like the piriform cortex, olfactory bulbs, hippocampal formation, vestibular nuclei, or the wulst, are among the brain regions often discussed as involved in avian navigation. However, despite a large literature identifying a prominent role of the dorsal anterior thalamic nuclei in mammalian spatial navigation, the same structure has not been identified as being important for birds. Here, we analyzed a possible role of the dorsal anterior thalamic nuclei in avian navigation by combining olfactory manipulations during the transport of young homing pigeons to a release site and c-Fos immunohistochemistry for the mapping brain activity. Findings show for the first time in birds that odor modulated neurons in the DLL subdivision of the dorsal anterior thalamic nuclei, previously shown to be involved in path integration in mammals, are actively involved in processing outward journey navigational information used to determine the home direction in pigeons. DLL involvement in processing path-based information, and its modulation by olfactory exposure, broadens our understanding of the neural pathways underlying avian navigation.